The Role Of Physical And Sport Education Class In Achieving Psychosocial Compatibility Among Final Class Of High School Students - Hachemane, Mohamed Elmokhtar (sports creativity, 2025)
This research aims to identify the levels of compatibility in the psychological and social dimensions of students in the final class of secondary school and to study the differences between those levels taking into account the gender variable. In order to achieve the objectives, the researcher adopted the descriptive approach to study the differences using two independent sample t-test. The research community represented (666) students in both genders in the municipality of Birkhadem in Algiers, Where (60) practitioners and (45) non-practitioners of physical and sport education session were randomly selected. A referred questionnaire was distributed to measure the psychological and social compatibility, the results showed the existence of statistically significant differences between practicing students and those who are not practicing.